Spontaneous compartment syndrome in a patient receiving oral_x000D_ anticoagulation therapy - (:unkn) unknown (My University, 2018)
Compartment syndrome (CS) is an emergency condition caused by muscle necrosis that can lead to locomotor dysfunctions.Intra-fascial bleeding of a limb due to direct trauma, reduction of fractures, or tight casting or bandages may causeacute CS. Although acute CS has many causes, few cases of spontaneous CS have been reported in the literature withoutany clear reasons. We present a case of a 53-year-old male who had a spontaneous CS in his right forearm. There was noany evidence of acute major or minor repetitive trauma. He had a history of taking multiple anticoagulants due to previousfemoral artery repair and still uses anticoagulants. After evaluation, we performed fasciotomy and removed an organizedhaematoma between the deep and superficial flexor tendons. The patient has recovered completely without any relapse atthe 2-year follow-up. Detailed information should be given to patients who are taking anticoagulants about acute CS.